The Education of Escobar Cruz: Sports, Identity and Masculinity in Middle School - Eligio Martinez Jr. (Middle Grades Review, 2018)
Some assert that middle school should be the stage in an individual’s educational trajectory where they begin to make plans for the future. For many young men of color, middle school becomes a stage where they begin to get off track academically. This is the story of Escobar Cruz, a young Latino male student, and his navigation through the 7th grade attempting to figure out who he is and who he wants to become. Escobar must choose between listening to his English Language Arts teacher or his peers and soccer coach and make decisions that will impact his future. Masculinity and school engagement are analyzed to explore the daily negotiations that young men of color engage in at schools.
Keywords: Latino Males; Middle School; Masculinity